Rotavirus y adenovirus causantes de síndrome diarreico en niños menores de 2 años de parroquias rurales. Alausí, Chimborazo. - Ñamiña Rodríguez, Jery David (2024)
Diarrheal syndrome is one of the most frequent health problems, particularly in the pediatric population. Diarrhea is caused by viral agents such as rotavirus and adenovirus, thus raising significant public health concerns worldwide. This study aimed to estimate the prevalence of rotavirus and adenovirus as causative agents of diarrheal syndrome in children under two years old in Alausí Canton. This research is descriptive, field-based, prospective, and cross-sectional. From a population of 200 infants, 67 fecal samples from children aged 0 to 24 months were selected based on inclusion and exclusion criteria. These samples were analyzed using the immunochromatographic technique for rapid diagnosis, demonstrating high sensitivity and specificity. Of the total samples analyzed, rotavirus was (0%), while adenovirus was 2.0% of cases. Additionally, data were collected on risk factors associated with diarrheal syndrome, such as the frequency of handwashing and water treatment practices before consumption. In conclusion, the prevalence of viral agents in the analyzed pediatric population has shown improvement due to the conditions and habits adopted by families. Furthermore, diarrheal syndrome can be caused not only by these viruses but also by other bacterial or parasitic pathogens.